2016
DOI: 10.1038/hr.2016.78
|View full text |Cite
|
Sign up to set email alerts
|

Association between social participation and hypertension among older people in Japan: the JAGES Study

Abstract: Hypertension is an important risk factor for cardiovascular disease, the leading cause of mortality in the world. Although previous studies have focused on individual-level behavioral risk factors associated with hypertension, there has been little research on how interacting with others, that is social participation, affects hypertension. To address this research gap, this study examined the association between social participation and hypertension in Japan, a country with a high prevalence of hypertension po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 48 publications
0
29
0
4
Order By: Relevance
“…The inverse association between social participation and hypertension observed in this study was in line with Yazawa et al , who showed in their cross‐sectional study in Japan that participating in horizontal organizations (i.e. groups that are characterized by non‐hierarchical, egalitarian relationships among group members; volunteer, sport and hobby groups in their study) once a month or more frequently was associated with a lower prevalence of hypertension among the Japanese older population (aged ≥ 65 years) . As we used information on similar types of community organizations/activities (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The inverse association between social participation and hypertension observed in this study was in line with Yazawa et al , who showed in their cross‐sectional study in Japan that participating in horizontal organizations (i.e. groups that are characterized by non‐hierarchical, egalitarian relationships among group members; volunteer, sport and hobby groups in their study) once a month or more frequently was associated with a lower prevalence of hypertension among the Japanese older population (aged ≥ 65 years) . As we used information on similar types of community organizations/activities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yazawa et al showed that participation in horizontal organizations (i.e. groups that are characterized by non‐hierarchical, egalitarian relationships among group members; volunteer, sport and hobby groups in their study) was inversely associated with hypertension among older people in Japan . Kamiya et al showed that participating in a greater number of organizations was associated with a lower odds of hypertension among the older population living in the UK …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Informal socializing—such as frequency of meeting with one’s friends—is considered a structural indicator of network contacts. Social participation means participation in community organizations [9]. …”
Section: Introductionmentioning
confidence: 99%